Working anytime and anywhere: a contemporary behavioral phenomenon - Schoellbauer, Julia; Kelliher, Clare; Hartner-Tiefenthaler, Martina (Frontiers, 2024)
Work flexibilization enables office employees and knowledge workers to work anytime and anywhere, including outside of their expected working times. In this Research Topic, we assemble seven original papers presenting theoretical considerations and empirical findings on the psychological implications of “working anytime and anywhere”. Drawing on border theory (Clark, 2000), Steffens et al. characterize the broad concept of “work-life-blending” in terms of four interlinked components: (I) the two domains of work and private life; (II) the dynamic interplay between these domains; and (III) the individual and (IV) interindividual dynamics (e.g., within a family) determining boundary segmentation strategies. The six other papers offer insights on “working anytime and anywhere” by discussing workers' flexible work activities (Jiang et al.; Ma et al.; Yeves et al.) and extended work activities (Hendrikx et al.; Mueller et al.; Schoellbauer et al.).
Editorial
Keywords: blurred boundaries; extended work; flexible work; flexible work arrangement; extended availability